Effects of Rossby waves breaking and atmospheric blocking formation on the extreme forest fire and floods in Eastern Siberia 2019 - Antokhina, Olga Yu; Antokhin, Pavel N.; Belan, Boris D.; Gochakov, Alexander V.; Martynova, Yuliya V.; Pustovalov, Konstantin N.; Tarabukina, Lena D.; Devyatova, Elena V. (Fire)
In 2019, the southern region of Eastern Siberia (located between 45 N and 60 N) experienced heavy floods, while the northern region (between 60 N and 75 N) saw intense forest fires that lasted for almost the entire summer, from 25 June to 12 August. To investigate the causes of these natural disasters, we analyzed the large-scale features of atmospheric circulation, specifically the Rossby wave breaking and atmospheric blocking events. In the summer of 2019, two types of Rossby wave breaking were observed: a cyclonic type, with a wave breaking over Siberia from the east (110 E-115 E), and an anticyclonic type, with a wave breaking over Siberia from the west (75 E-90 E). The sequence of the Rossby wave breaking and extreme weather events in summer, 2019 are as follows: 24-26 June (cyclonic type, extreme precipitation, flood), 28-29 June and 1-2 July (anticyclonic type, forest fires), 14-17 July (both types of breaking, forest fires), 25-28 July (cyclonic type, extreme precipitation, flood), 2 and 7 August (anticyclonic type, forest fires). Rossby wave breaking occurred three times, resulting in the formation and maintenance of atmospheric blocking over Eastern Siberia: 26 June-3 July, 12-21 July and 4-10 August. In general, the scenario of the summer events was as follows: cyclonic Rossby wave breaking over the southern part of Eastern Siberia (45 N-60 N) caused extreme precipitation (floods) and led to low gradients of potential vorticity and potential temperature in the west and east of Lake Baikal. The increased wave activity flux from the Europe-North Atlantic sector caused the anticyclonic-type Rossby wave breaking to occur west of the area of a low potential vorticity gradient and north of 60 N. This, in turn, contributed to the maintenance of blocking anticyclones in the north of Eastern Siberia, which led to the intensification and expansion of the area of forest fires. These events were preceded by an increase in the amplitude of the quasi-stationary wave structure over the North Atlantic and Europe during the first half of June.